Needs to Change Behaviour in Households Producing Lots of Food Waste - Margit Narva; Jarmo Alarinta; Gun Wirtanen (International Journal of Food Studies)
The purpose of this research was to investigate avoidable food waste among households of students studying in higher education in Sein¨ajoki. The focus was to quantify the avoidable food waste in different-sized households. The focus was also to specify food categories wasted, and the main reasons for avoidable food waste accumulated. The participating households weighed all their food waste during the one-week monitoring period recording the data on an Excel spreadsheet. The university students taking part in the study were introduced to the work by video instruction. In total 421 households with 918 persons took part in this study. It was found that the average amount of avoidable food waste was equal to 25.2 kg/person/year. In single person households, the amount was 36.6 kg/year. The amount for households with five or more persons was 80.0 kg/household i.e. 14.1 kg/person. This research showed that 25 % of the households caused 56 % of the avoidable food waste, which means that main efforts should be targeted to this ’heavy wasting’ group. One way of improving the good practices would be to share good habits related to lowering food waste among university students through peer learning. This study is aimed to awaken the ’heavy wasting’ university student to change their attitude and behaviour.